KURIKULUM 2013 DALAM PERSPEKTIF FILSAFAT PENDIDIKAN PROGRESSIVISME - Al Faris, Fitri (Jurnal Filsafat "WISDOM", 2015)
The educational curriculum in Indonesia has grown recent times but the philosophical foundation used rarely explored. The philosophical foundation used became an interesting thing. Through the clear philosophical foundation, direction and purpose of education became clear too. This study found that the nature of the educational curriculum 2013 were increasing changes base towards attitudes, knowledge and skills of the learners themselves in order to create a good character education. The goal to be achieved through the curriculum 2013 were producing creative and innovative generations to minimize poverty, ignorance and backwardness civilization. It has an eclectic incorporative philosophical foundation which means taking elements from education philosophy ideologies integrated with the national educational system. Progressivism as one of the schools of philosophy of education has a dominant part in the curriculum 2013 proved through the education system that is much focused to the students as the subjects of education, the teacher as a facilitator and the integrated lessons in one unit. The curriculum 2013 shows that the students must be taught in accordance with the developmental era. It will prevent producing obsolete generations. There are three main competencies of the students should be assessed as a whole things (attitudes, knowledge and skills).